SOIL METAGENOMICS - Sugitha, T. C. K.; Binodh, Asish K.; Ramasamy, K.; Sivakumar, U. ([S.l.] : CRC PRESS, 2020)
This book focuses on the recent advents and technological breakthroughs in metagenomic approaches coupled with their applications in agriculture. The intended audience include soil and environmental microbiologists, molecular biologists and policy makers. The book expertly describes the latest fourth generation metagenomic technologies from sample collection to data analysis, metatranscriptomic, metaproteomic and metabolomics studies Note: T& F does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.
1 Introduction To Metagenomics 2 Soil Metagenomics -- The Culture Independent Insight 3 Techniques in Soil Metagenomics 4 Accessing the Soil Metagenome 5 Construction of Soil Metagenomic Libraries 6 Enrichment Strategies of Soil Metagenome 7 Metagenomic Pyrosequencing and Microbial Identification 8 Metagenomic Gene Discovery 9 Taxonomic and Functional Diversity of Microbial Communities 10 Metagenomics and Ecology 11 Mobile Metagenomics 12 Viral Metagenomics -- Generation of Viral Metagenome 13 Mapping the Virus World Through Metagenomics 14 Functional Viral Metagenomics 15 Metagenomics and Integrative 'Omics' in Bioremediation 16 Metagenomics in White Biotechnology 17 Metagenomics in Agriculture 18 Bioinformatics in Metagenomics 19 Nanotechnology in Metagenomics 20 The Future of Metagenomics
OCLC-licensed vendor bibliographic record.
Keywords: Soil science; Soil microbiology; Metagenomics; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / Soil Science; TECHNOLOGY / Agriculture / Sustainable Agriculture